Mild oxidative stress protects against chemotherapy-induced hair loss - Zhang, Yusheng; Jimenez, Joaquin J. (Frontiers in Oncology, 2023)
Chemotherapy induces hair loss in most cancer patients who undergo treatment, which causes them significant psychosocial trauma. Scalp cooling has demonstrated some efficacy in attenuating chemotherapy-induced alopecia, but response rate varies between patients and chemotherapy class. Here, we showcase in rats a proof-of-concept treatment of using subcutaneous hydrogen peroxide and cumene hydroperoxide injections to provide total protection from hair loss against multiple classes of chemotherapy. We found that subcutaneous peroxides induce cell cycle arrest via P53 activation, thereby protecting hair follicles from the cytotoxic effects of chemotherapy on actively dividing cells. This treatment represents a highly effective and accessible way for cancer patients to maintain quality of life while undergoing treatment for cancer.